The Effect Of Self-Efficacy And Creative Thinking Skills On Achievement In Mathematics Using Structural Equation Modeling (Sem) - Rosiatuningsih; Norma Ayuwanda R; Wanda Nugroho Y (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
The background of this study is grounded in the importance of strengthening students' internal factors that contribute to success in mathematics learning, particularly self-efficacy and creative thinking skills. These variables foster students' confidence, encourage them to explore diverse problem-solving strategies, and improve mathematics learning achievement. Employing a quantitative approach with Structural Equation Modeling (SEM) using IBM SPSS AMOS software, this study examined the effects of self-efficacy and creative thinking skills on mathematics learning achievement. The participants consisted of 200 students from SMKN 1 Purwokerto. The model evaluation indicated an excellent fit with the observed data, reflected by a CMIN/DF value of 1.086 with a probability of 0.325, a Comparative Fit Index (CFI) of 0.995, and a Root Mean Square Error of Approximation (RMSEA) of 0.022. Creative thinking skills significantly influenced mathematics learning achievement, with an estimated coefficient of 0.324 (p = 0.002). Furthermore, self-efficacy also had a significant positive effect on mathematics learning achievement (estimate = 1.247, p = 0.020). These findings confirm that strengthening students' self-efficacy and creative thinking skills can optimize mathematics learning achievement and provide practical implications for vocational school teachers in designing more effective mathematics learning.